PENGARUH LEMBAGA KEUANGAN MIKRO TERHADAP PERTUMBUHAN SEKTOR PERTANIAN INDONESIA - Pasaribu, Yusnarto Fizai Atmojo; Aryanto, Oktama Gusti Yudha; Saraswati, Birgitta Dian (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
The agricultural sector is a crucial sector in the Indonesian economy, this can be seen from its contribution to Gross Regional Domestic Product in 2022 of 12.40%. One of the problems faced by farmers is in terms of capital. The aim of this research is to analyze the influence of the number of MFIs and the financing provided by MFIs in Indonesia. This research uses quantitative methods with panel data regression analysis techniques for 2019-2022 in 21 provinces in Indonesia. The results of this research show that the number of microfinance institutions has no effect on the growth of the agricultural sector, this occurs because the existence of microfinance institutions is not evenly distributed in Indonesia. Then the financing provided by microfinance institutions has a negative effect on the growth of the agricultural sector, this is thought to be due to farmers' moral hazard and weak regulations that form the legal basis for MFIs.